Cellular Lightweight Concrete - Dhengare, Sagar W.; Dandge, Ajay L.; Nikhade, H. R. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
Cellular Light weight Concrete (CLWC) is not a new invention in concrete world. It has been known since ancient times. It was made using natural aggregates of volcanic origin such as pumice, scoria, etc. The Greeks and the Romans used pumice in building construction. Lightweight concrete can be defined as a type of concrete which includes an expanding agent in that it increases the volume of the mixture while giving additional qualities such as inability and lessened the dead weight. The usage of Cellular Light-weight Concrete (CLC) blocks gives a prospective solution to building construction industry along with environmental preservation.